2016
DOI: 10.1007/s00192-016-3212-4
|View full text |Cite
|
Sign up to set email alerts
|

Urinary retention in female OAB after intravesical Botox injection: who is really at risk?

Abstract: Introduction and hypothesisIntravesical onabotulinumtoxinA (Botox) injections are effective for the treatment of idiopathic overactive bladder (OAB) symptoms. The aim of our study was to assess the predisposing factors for urinary retention in women with OAB after intravesical Botox injection.MethodsAll participants were women of European descent with idiopathic OAB. OnabotulinumtoxinA (100 U) was administered in 20 intra-detrusor injections. Analysis was performed based on the results of safety assessments ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
7
32
2
Order By: Relevance
“…59 Clean intermittent catheterization may also become necessary after later injections even if it was not initially required. Other factors that may increase the risk of CIC include older age (>61-76 years) (LE 2, GR B), 43,60 frailty (LE 2, GR B) 43 and higher parity (particularly a higher number of vaginal deliveries; LE 2, GR B). 60 A recent study has shown that BMI and concomitant comorbidities do not significantly influence PVR volumes and the risk of CIC, even though one would expect that these factors could provoke safety issues.…”
Section: Predictive Factors For Cicmentioning
confidence: 99%
See 3 more Smart Citations
“…59 Clean intermittent catheterization may also become necessary after later injections even if it was not initially required. Other factors that may increase the risk of CIC include older age (>61-76 years) (LE 2, GR B), 43,60 frailty (LE 2, GR B) 43 and higher parity (particularly a higher number of vaginal deliveries; LE 2, GR B). 60 A recent study has shown that BMI and concomitant comorbidities do not significantly influence PVR volumes and the risk of CIC, even though one would expect that these factors could provoke safety issues.…”
Section: Predictive Factors For Cicmentioning
confidence: 99%
“…Other factors that may increase the risk of CIC include older age (>61-76 years) (LE 2, GR B), 43,60 frailty (LE 2, GR B) 43 and higher parity (particularly a higher number of vaginal deliveries; LE 2, GR B). 60 A recent study has shown that BMI and concomitant comorbidities do not significantly influence PVR volumes and the risk of CIC, even though one would expect that these factors could provoke safety issues. 60 Nevertheless, Wang et al showed that patients with diabetes have a significantly increased incidence of PVR volumes greater than 150 mL (60.4%) compared with nondiabetic patients (33.3%; LE 3, GR C).…”
Section: Predictive Factors For Cicmentioning
confidence: 99%
See 2 more Smart Citations
“…An unwillingness or inability to perform CIC does cause some patients to reject the option of bladder onaBoNT‐A. Recently, age, higher parity, and higher number of vaginal deliveries were all reported as factors that predisposed women to start CIC after onaBoNT‐A . Also, preoperative PVR was associated with increased risk of postoperative urinary retention after onaBoNT‐A injection .…”
Section: Introductionmentioning
confidence: 99%